Imaging antimatter with a Micromegas detector - Mäckel, V; Radics, B; Dupre, P; Higaki, H; Kanai, Y; Kuroda, N; Matsuda, Y; Nagata, Y; Tajima, M; Widmann, E; Yamazaki, Y (Nuclear Inst. and Methods in Physics Research, B, 2018)
The ASACUSA collaboration aims at measuring the ground state hyperfine splitting of antihydrogen for probing fundamental symmetries. A cryogenic trap for mixing antiprotons and positrons serves as an antihydrogen source for in-flight spectroscopy. In order to be able to monitor the antihydrogen formation process, a dedicated Micromegas tracking detector has been designed and built to record the annihilation distribution in the trap. In this paper, we present the first results from antiproton annihilation data recorded with the Micromegas, together with a description of the event reconstruction algorithm.
Keywords: 3D tracking; Annihilation; Antiproton; Micromegas tracker; Track reconstruction

ASACUSA MUSASHI: New progress with intense ultra slow antiproton beam - Imao, H.; Tarek, M.; Michishio, K.; Enomoto, Y.; Shimoyama, T.; Kanai, Y.; Kuroda, N.; Mohri, A.; Higaki, H.; Saitoh, H.; Torii, H.A.; Nagata, Y.; et al. (Hyperfine Interactions, 2009)
Keywords: Antihydrogen; Antiproton; Positron

On the double ionization of helium by very slow antiproton impact - Knudsen, H.; Kristiansen, H.-P. E.; Thomsen, H. D.; Uggerhøj, U. I.; Ichioka, T.; Møller, S. P.; Hunniford, C. A.; McCullough, R. W.; Charlton, M.; Kuroda, N.; Nagata, Y.; Torii, H. A.; et al. (Proceedings of the Fourth International Conference on Elementary Processes in Atomic Systems, 2009)
Keywords: Antiproton; CERN AD; Electron correlation; Ionization